Pengaruh Penggunaan Masker Singkong Kuning terhadap Perawatan Kulit Wajah Kering, Peningkatan Kelembapan, dan Kesehatan Kulit - Hesti Efrina; Mitra Lusiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Dry facial skin is a common condition characterized by dull, flaky skin that is prone to wrinkles. This often reduces a person's self-confidence, making the search for solutions to treat dry skin an important concern. One natural remedy believed to help address dry skin issues is yellow cassava, which is rich in starch and nutrients. This study aims to determine whether the use of yellow cassava masks affects the moisture level of dry facial skin. The research was conducted using a quasi-experimental experimental approach, involving two groups: a control group and an experimental group. Each group received treatment once a week for four weeks. The experimental group used yellow cassava masks, while the control group received no treatment. Moisture levels of the facial skin were assessed before and after the treatment. The sample consisted of 6 participants, selected through purposive sampling. The main data was obtained through direct observation and documentation, and then analyzed using normality tests, homogeneity tests, and hypothesis tests. The results showed that the average moisture level of the control group at the end of the study was 41.7%, while the experimental group showed an increase, with an average of 44.1%. However, hypothesis testing indicated that the difference was not statistically significant. Based on these findings, it can be concluded that the use of yellow cassava masks in the short term does not show a significant effect on the moisture level of dry facial skin. The researchers suggest that further studies should be conducted over a longer period to achieve more optimal results and to gain a deeper understanding of the benefits of yellow cassava masks in treating dry facial skin.